If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -19 = 2x + 11 Reorder the terms: -19 + 9x = 2x + 11 Reorder the terms: -19 + 9x = 11 + 2x Solving -19 + 9x = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -19 + 9x + -2x = 11 + 2x + -2x Combine like terms: 9x + -2x = 7x -19 + 7x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 -19 + 7x = 11 + 0 -19 + 7x = 11 Add '19' to each side of the equation. -19 + 19 + 7x = 11 + 19 Combine like terms: -19 + 19 = 0 0 + 7x = 11 + 19 7x = 11 + 19 Combine like terms: 11 + 19 = 30 7x = 30 Divide each side by '7'. x = 4.285714286 Simplifying x = 4.285714286
| 6x-x=60+30 | | x^2-6x+153=0 | | 16a*2-14a+1a*2-3a= | | 25-5x-18-12x=10 | | x^2-6+153=0 | | 15x+6-(X+2)= | | 0.25(m+5)=-1.5 | | 12x=10x+60 | | 10y=-22 | | 1+6h=2+4h | | 14x-5=10x+7 | | 7y-14=21 | | =k^2+4k+4 | | -7(x+5)=35 | | 5w-4=6 | | 1+4/5c=7 | | 6=-3/5(n+8) | | 6s+2s-3s+-6= | | 5x=2(9-x) | | 8-3x-8+5x= | | -x/5+7=-16 | | 3p+6=14 | | 3x-15=7x+7 | | 12x+4=3(2x+5)-8 | | =7v^2+35v-42 | | 3y+2y+8y+27-12y-16-2y= | | 35.80+5.90=220.70 | | 3u+8-2(-2u-2)=3(u-2) | | 5x+34=15x-64 | | z+9=2z+7 | | -7=9-5/6a | | a+15=3a+11 |